Image editing with Camera Raw in Adobe Photoshop CS5 : learn by video - Aaland, Mikkel, 1952- (Peachpit Press, 2011)
"This innovative product uses interactive video to teach digital photographers how to use the Adobe Camera Raw plugin in Adobe Photoshop CS5. Users will learn the ins and outs of the Adobe Camera Raw workspace and how to use preview and analysis tools to determine how to adjust an image. The video demonstrates how to automatically and manually optimize image tones and how to get the correct white balance, as well as how to optimize a batch of images. Viewers will learn how to get localized control over an image with the adjustment brush and how to make a dramatic sky with the graduated filter. Sharpening is an important part of image processing, and this video covers the essentials of this complex subject. Award-winning photographer Mikkel Aaland presents three hours of exceptional quality video tutorials, complete with lesson files, assessment quizzes, and review materials. The video is wrapped in a unique interface that allows the viewer to jump to any topic and also bookmark individual sections for later review. The unique Watch-and-Work mode shrinks the video into a small window to allow the student to work alongside in Photoshop. Project files used in the lessons are included on the disc so viewers can practice what they've learned, and interactive review questions help reinforce freshly gained knowledge."--Resource description page.